The research applicable to elaboration of new generation of effective medicinal drugs using encapsulation of classic substances into nanocontainers - V. I. Shvets; A. I. Lyutik (Тонкие химические технологии)
Biopharmaceutical technologies using phospholipids for the development of a new generation of pharmaceutical formulations are considered. Industrial methods for isolating phosphatidylcholine from egg yolk and cardiolipin from the heart muscle were implemented at the Biolek company (Kharkov). The industrial production of a number of phospholipid fractions has been mastered too. The latest data concerning the application of nanocontainers for loading classic drugs during the design of modern effective drug formulations are reported. These formulations are used to improve the results of treatment, to provide the targeted drug delivery into pathological foci, to prolong the action time, and to increase the drug solubility. Among the aforementioned containers, special emphasis should be given to liposomes, nanosomal polymeric formulations based on polybutylcyanoacrylates or on polylactides, and spherical amorphous nanoparticles formed from birch bark triterpenoids. The modern state of researches performing by scientific team headed by academician V.I. Shvets is also presented.